Anterior cruciate ligament injuries in female athletes. Part 2, A meta-analysis of neuromuscular interventions aimed at injury prevention - Hewett, T. E.; Ford, K. R.; Myer, G. D. (The American Journal of Sports Medicine, 2006)
Female athletes have a 4 to 6 times higher incidence of anterior cruciate ligament injury than do male athletes participating in the same landing and pivoting sports. This greater risk of anterior cruciate ligament injury, coupled with a geometric increase in participation (doubling each decade), has led to a significant rise in anterior cruciate ligament injuries in female athletes. The gender gap in anterior cruciate ligament injury, combined with evidence that the underpinnings of this serious health problem are neuromuscular in nature, leads to the development of neuromuscular interventions designed to prevent injury. A systematic review of the published literature yielded 6 published interventions targeted toward anterior cruciate ligament injury prevention in female athletes. Four of 6 significantly reduced knee injury incidence, and 3 of 6 significantly reduced anterior cruciate ligament injury incidence in female athletes. A meta-analysis of these 6 studies demonstrates a significant effect of neuromuscular training programs on anterior cruciate ligament injury incidence in female athletes (test for overall effect, Z = 4.31, P < .0001). Examination of the similarities and differences between the training regimens gives insight into the development of more effective and efficient interventions. The purpose of this "Current Concepts" review is to highlight the relative effectiveness of these interventions in reducing anterior cruciate ligament injury rates and to evaluate the common training components between the training studies. In addition, the level of rigor of these interventions, the costs and the difficulty of implementation, the compliance with these interventions, and the performance benefits are discussed. This review summarizes conclusions based on evidence from the common components of the various interventions to discuss their potential to reduce anterior cruciate ligament injury risk and assess their potential for combined use in more effective and efficient intervention protocols.